MARKET ORIENTATION: URGENSI DAN PERANANNYA DALAM MENINGKATKAN PERFORMANCE UKM (USAHA KECIL MENENGAH) DI INDONESIA - Purnamasari, Heny Rita (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
The large population and the quality is the basic capital andthe potential for improvement in all fields of development. A large number ofthe population of productive age group compared with the non-productiveage group can also provide benefits for national development, especially inthe economic sector. “Small and medium enterprises (SME) are the backboneof industrial development. It is very important for both developed anddeveloping country Small and medium enterprises alwaysrepresented themodel of economic development, which emphasized high contribution todomestic production, employment generation”. Marketing orientation can bedescribed as a culture in which organizations strive to create superior valuefor their customers (and superior performance for the business) by focusingon customer needs and long-term profitability. Some studies have found thatfirms with a high degree of marketing orientation experience improvedperformance.Keywords : SME, Small Medium Entreprises, Market Orientation